Assessment of knowledge, attitudes and practices (KAP) among food handlers at residential colleges and canteen regarding food safety - Siow, Oi Nee; Norrakiah Abdullah Sani, (Universiti Kebangsaan Malaysia, 2011)
residential colleges and canteen in the main campus of Universiti Kebangsaan Malaysia regarding the aspect of food hygiene and safety. Sixty five food handlers from two residential colleges’ cafeterias and one Faculty of Science and Technology’s canteen were involved in the study. The data were collected from the food handlers through the methods of questionnaire and analyzed using the SPSS version 12.0. In general, the respondents’ knowledge was moderate with mean point of 57.8%. However, they have good knowledge on personal hygiene and definition of foodborne diseases with mean point of 93.85% and 73.85%, respectively. On the contrary, their knowledge on food storage and preparation temperatures was poor with only 28%. Respondents showed positive attitudes towards two categories of questions in the aspect of food safety and hygiene (76.9%); foodborne prevention and control (70.8%). Majority of the respondents have an average practices in all parts of the questions. Analysis tests showed significant difference (p<0.05) between the relationship of respondents’ knowledge with their working experiences (p=0.008), attitudes with training attended (p=0.006) and practices with gender (p=0.032). There was significant difference for knowledge based on cafeteria (p=0.000). In conclusion, amongst the three levels, respondents showed only good attitudes in food handling and all the cafeterias in this survey need to increase the hygiene level of their food handlers’ hand and environment of the premises.